2023
DOI: 10.1002/advs.202206139
|View full text |Cite
|
Sign up to set email alerts
|

SOX17 is a Critical Factor in Maintaining Endothelial Function in Pulmonary Hypertension by an Exosome‐Mediated Autocrine Manner

Abstract: Endothelial dysfunction is considered a predominant driver for pulmonary vascular remodeling in pulmonary hypertension (PH). SOX17, a key regulator of vascular homoeostasis, has been found to harbor mutations in PH patients, which are associated with PH susceptibility. Here, this study explores whether SOX17 mediates the autocrine activity of pulmonary artery ECs to maintain endothelial function and vascular homeostasis in PH and its underlying mechanism. It is found that SOX17 expression is downregulated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Previous studies have reported that genes such as Ki67 [ 20 ] /Egfr [ 21 ] /Sox17 [ 22 ] /Cyclins [ 23 ] are actively expressed in proliferating cells, indicating that the cells are in an active state of proliferation. To investigate the role of IGFBP7 on endothelial cell growth, we first examined the role of IGFBP7 in the injured endothelial model (LPS stimulation).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that genes such as Ki67 [ 20 ] /Egfr [ 21 ] /Sox17 [ 22 ] /Cyclins [ 23 ] are actively expressed in proliferating cells, indicating that the cells are in an active state of proliferation. To investigate the role of IGFBP7 on endothelial cell growth, we first examined the role of IGFBP7 in the injured endothelial model (LPS stimulation).…”
Section: Resultsmentioning
confidence: 99%
“…Of particular interest to us are documented instances of exosomal autocrine secretion. For instance, SOX17 has been demonstrated to maintain endothelial function inpulmonary hypertension through the process of exosomal autocrine secretion (Zou et al, 2023). Furthermore, exosomes that transport plasma gelsolin (pGSN) promote the survival of ovarian cancer cells through both autocrine and paracrine mechanisms, transforming chemosensitive cells into resistant counterparts (Asare-Werehene et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sangam et al 16 reported that SOX17 deficiency inhibits mitochondrial bioenergetics and induces PAH partly via HIF-2α signaling. Zou et al 32 identified SOX17-associated exosomes including microR-224-5p and microR-361-3p improve endothelial function. Taken together, these studies highlight the critical role of SOX17 in maintaining endothelial function and repressing PH development.…”
Section: Discussionmentioning
confidence: 99%